Hubungan Antara Tingkat Pendidikan dan Pendapatan Karyawan dengan Pengetahuan dan Sikap Keamanan Pangannya pada Tempat Makan di DKI Jakarta - Arie Norman Riandi; Winiati Pudji Rahayu; Siti Nurjanah (Institut Pertanian Bogor, 2021)
Food safety is an important aspect of consumption behavior, especially for employees in the office. Lack of food safety knowledge and awareness can endanger the health and reduce the productivity of employee. This study aims to describe the level of food safety knowledge and attitudes of employees at food stalls as well as their preferences for lunch at office environment, determine the effectiveness of information media as a source of food safety information and also the role of the government in food safety education and food safety supervision at food stalls. This study used an online questionnaire with 405 respondents who work in the DKI Jakarta. The data collected were analyzed statistically using the SPSS program. The results showed that the characteristics of the employees, such as education level and nett income level, had an effect on the food safety knowledge level and food safety attitudes at the food stalls. Most of employees (87,7%) have a good level of food safety knowledge and 67,7% of employees also have a good level of food safety attitude at food stalls. The results of the Spearman correlation test showed that the level of food safety knowledge and attitude at food stalls was correlated with the level of education and nett income. Most of the employees (37,8%) choose the canteen as a place to eat in the office and some choose food stalls (16,0%) and restaurants (10,1%). Information media considered effective enough for spreading the information of food safety according to employees was social media. Keywords: attitudes, consumption behaviour, employees, food safety, knowledge